Relationship between grade point average for English courses and English competency assessment of students at Rajamangala University of Technology Suvarnabhumi in academic year 2017 - Kasipan, Wuttichai; Kheawmanee, Chartchai; Boonsan, Somjai (RMUTSB ACADEMIC JOURNAL (HUMANITIES AND SOCIAL SCIENCES), 2020)
The purposes of the research are to study and forecast the relationship between grade point for each English course in the general education courses and English competency assessment results of undergraduate students of Rajamangala University of Technology Suvarnabhumi in the academic year 2017 by using point-biserial correlation and binary logistic regression analysis. The sample group in this study was chosen through specific sampling which comprised 1,345 undergraduate students of Rajamangala University of Technology Suvarnabhumi in the academic year of 2017 at their final year of the regular 4-year and 5-year program, who participated in the English competency assessment test. The result of the study showed that grade point variable for Everyday English course, Reading English for Learning course, Communicative English Writing course, and Preparing English for Work course had relationships with English competency assessment results with a statistically significant level of 0.05. In addition, the forecasting of the English competency assessment results found that the grade point variables that could forecast the passing the English competency assessment criteria of students at Rajamangala University of Technology Suvarnabhumi were the grade point of Everyday English, the grade point of Reading English for Learning and the grade point of Communicative English Writing. By contrast, the variable of the grade point of Preparing English for Work could not forecast the passing of English competency assessment criteria of the students at Rajamangala University of Technology Suvarnabhumi. Considering the relationship, it was found that if the students have an Everyday English score increased by 1 point, there is an opportunity to pass the English language competency by 1.23 times whereas the students who have a score of Reading English for Learning score increased by 1 point, there is an opportunity to pass the English language competency by 1.87 times, and students who have Communicative English Writing score increased by 1 point will have an opportunity to pass the English language performance by 1.57 times. Controlling other variables to be stable, the prediction logit can be written as follows: Predicted logit =-1.54+0.21* (Everyday English)+0.63* (Reading English for Learning)+0.45* (Communicative English Writing). The equation can predict independent variables by 18.70 percent.